2006
DOI: 10.1029/2005jd006208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cirrus clouds on the diurnal cycle of tropical deep convective clouds

Abstract: [1] The cirrus clouds tightly connected with tropical deep convective clouds can extend and persist for some hours after the deep convective clouds themselves dissipate. This can result in time lags of the diurnal cycle of deep convective clouds detected from infrared satellite measurements with different brightness temperature thresholds because different amounts of cirrus clouds contaminate the measurement. The diurnal cycles of rain from the Tropical Ocean-Global Atmosphere (TOGA) radar during the Tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 59 publications
12
60
0
Order By: Relevance
“…Those investigations demonstrated that rain usually increases progressively as the cloud-top temperature decreases [4]. However, some studies shows that cold cloud TB does not necessarily imply precipitation due to the existence of cold cloud tops [1,5]. The relationship between cloud characteristics and their generated precipitation remains unclear and needs further detailed analysis at the pixel scale [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Those investigations demonstrated that rain usually increases progressively as the cloud-top temperature decreases [4]. However, some studies shows that cold cloud TB does not necessarily imply precipitation due to the existence of cold cloud tops [1,5]. The relationship between cloud characteristics and their generated precipitation remains unclear and needs further detailed analysis at the pixel scale [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…deep convective clouds T 11 < 220 K, and cirrus anvils clouds 220 K < T 11 < 260 K). It has been demonstrated that a noticeable diurnal cycle of both deep convective clouds, high cold clouds, and upper tropospheric humidity (UTH) is present over land and ocean regions associated with convective activity (Hong et al, 2006;Chung et al, 2007). The UTH is observed to lag the peak of high cloud cover by several hours which, in turn, lags the peak of deep convective cloud occurrence (Horváth and Soden, 2008;Sohn et al, 2008;Zelinka and Hartmann, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies are based on geostationary infrared (IR) data (e.g. Soden, 2000;Tian et al, 2004;Chung et al, 2007), but also combinations of IR and radar data from the Tropical Rainfall Measuring Mission (Hong et al, 2006;Liu and Zipser, 2008a) as well as IR and passive microwave measurements (Zelinka and Hartmann, 2009) have been used. Typically, IR brightness temperatures at 6.7 µm are used to estimate the clear sky mean relative humidity between 500 and 200 hPa (Soden and Bretherton, 1993), and various thresholds of the 11 µm window channel are used to estimate occurrence frequencies of various cloud types (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is not necessarily the case for H 2 O and the influence from below would tend to increase retrieved mixing ratios at 100 hPa. This influence is more pronounced over land since convection has no strong diurnal cycle over ocean (Hong et al, 2006) and would thus explain the smaller correlation of nighttime IWC and H 2 O over land.…”
Section: Discussionmentioning
confidence: 99%
“…However, the anticorrelation is higher over Indonesia and the Pacific Ocean than over South America. Convection has a pronounced diurnal cycle over land which is absent over ocean (Hong et al, 2006). This may explain the differences in correlation over land and ocean since we only use nighttime CALIPSO measurements.…”
Section: Anticorrelation Of Water Vapor and Cirrus Cloudsmentioning
confidence: 99%